The Detrimental Effects of Sedentary Lifestyle on Human Health - Alicja Grzelak (Journal of Education, Health and Sport)
Introduction: Sedentary lifestyles have become increasingly prevalent in modern societies, posing significant threats to human health. Technological advancements and the shift towards desk-based occupations have contributed to a substantial decline in physical activity, leading to a rise in various diseases. The detrimental effects of a sedentary lifestyle are far-reaching, impacting physical, mental, and cognitive aspects of well-being.